DOI: 10.36837/chapman.000176
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Traumatic Stress in Teachers and School Communities Impacted by the Opioid Epidemic

Abstract: Secondary Traumatic Stress in Teachers and School Communities Impacted by the Opioid Epidemic by Anne Steketee People who support others who have experienced trauma, like nurses, doctors, social workers, or first responders can sometimes be affected by a type of stress called secondary traumatic stress (STS). Although the effect of STS has been studied in helpers like social workers and medical professionals, the prevalence and characteristics of STS in teachers have not been studied extensively and are less u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 138 publications
(362 reference statements)
0
2
0
Order By: Relevance
“…There are multiple within-school pathways through which community opioid presence may affect children’s educational outcomes. To start, scholars have documented the consequences of the opioid epidemic for teachers’ stress and well-being, noting the dearth of resources and training provided to educators in opioid-affected communities (Anderson, Troilo, and Tack 2019; Steketee 2020; Welby 2019). For example, in surveys of more than two thousand educators in West Virginia, Anderson, Troilo, and Tack (2019) found that more than 70 percent reported “emotional exhaustion, cynicism and a lack of personal accomplishment related to the changing classroom dynamics created by the opioid crisis.” Given widely documented relations between teachers' stress and turnover rates (e.g., Sass, Seal, and Martin 2011), as well as the negative consequences of teacher stress and turnover for children’s academic development (Hagermoser Sanetti et al 2021), opioid-related teacher stress would be expected to harm students’ classroom learning.…”
Section: Community Opioid Prevalence and Children’s Educational Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple within-school pathways through which community opioid presence may affect children’s educational outcomes. To start, scholars have documented the consequences of the opioid epidemic for teachers’ stress and well-being, noting the dearth of resources and training provided to educators in opioid-affected communities (Anderson, Troilo, and Tack 2019; Steketee 2020; Welby 2019). For example, in surveys of more than two thousand educators in West Virginia, Anderson, Troilo, and Tack (2019) found that more than 70 percent reported “emotional exhaustion, cynicism and a lack of personal accomplishment related to the changing classroom dynamics created by the opioid crisis.” Given widely documented relations between teachers' stress and turnover rates (e.g., Sass, Seal, and Martin 2011), as well as the negative consequences of teacher stress and turnover for children’s academic development (Hagermoser Sanetti et al 2021), opioid-related teacher stress would be expected to harm students’ classroom learning.…”
Section: Community Opioid Prevalence and Children’s Educational Outcomesmentioning
confidence: 99%
“…There are multiple within-school pathways through which community opioid presence may affect children's educational outcomes. To start, scholars have documented the consequences of the opioid epidemic for teachers' stress and well-being, noting the dearth of resources and training provided to educators in opioid-affected communities (Anderson, Troilo, and Tack 2019;Steketee 2020;Welby 2019). For example, in surveys of more than two thousand educators in West Virginia, Anderson, Troilo, and Tack (2019) found that more than 70 percent reported "emotional exhaustion, cynicism and a lack of personal accomplishment related to the changing classroom dynamics created by the opioid crisis."…”
Section: Community Opioid Prevalence and Children's Educational Outcomesmentioning
confidence: 99%